Waist circumference and insulin levels in obese children - Vina Paramitha Cempaka; I Gusti Lanang Sidiartha (Indonesian Pediatric Society, 2017)
Background Childhood obesity is one of the most serious public health challenges of the 21st century. Its prevalence has increased at an alarming rate. Overweight and obese children are prone to obesity in adulthood and to developing non-communicable diseases (NCDs) like diabetes and cardiovascular diseases at a younger age. Increased waist circumference has been shown to contribute to the risk of metabolic syndrome in obese adults.Objective To assess for a correlation between waist circumference and insulin level in obese children.Methods In this cross-sectional study, obese children aged 6-10 years were included by consecutive sampling. We excluded children with infectious disease, malignancy, dyslipidemia, type 2 diabetes mellitus, or those who had not fasted before the blood draw. Subjects underwent waist circumference and fasting blood glucose measurements. Serum insulin levels were examined by enzyme-labeled chemiluminescent immunometric assay,after subjects had fasted for 10-14 hours. Data were analyzed by correlation analysis.Results Subjects had a mean waist circumference of 80.2 cm (SD 7.2) and mean insulin level of 10.70 (SD 7.5). ÂµIU/mL Pearsonâ€™s correlation test revealed a significant, moderately positive correlation between waist circumference and elevated insulin level (r=0.45; P=0.006).Conclusion Waist circumference and insulin level have a significant, moderate, positive correlation in obese children. As such, waist circumference may be a simple method for early detection of hyperinsulinemia, as a risk factor for metabolic syndrome.